Mental Models for Scientists Communicating With the Public - MORGAN, KARA; FISCHHOFF, BARUCH (Issues in science and technology, 2023)
Morgan and Fischhoff discuss the challenges faced by scientists in effectively communicating with the public and the need for a better approach to bridge the gap between scientific knowledge and public understanding. Over the years, scientists have made remarkable contributions but often feel unappreciated due to a lack of trust from the public and policymakers. They emphasize the need for a shift from the "deficit model" (which assumes the public lacks knowledge) to the "dialogue model" (focused on two-way communication). One effective approach for communicating science is risk communication, which involves presenting scientific information in a relatable way to help individuals make informed decisions about potential risks. This model requires ongoing dialogue with the public to understand their concerns and adapt messages accordingly. They also tackle three key barriers hindering effective communication: scientists are trained to communicate with other experts, not the public; teaching experience doesn't prepare scientists to engage with non-experts; and scientific disciplines often work in isolation, while risk communication requires interdisciplinary collaboration.